Evaluating the Quality of School Health Services in Secondary Schools Within Gbarain/Ekpetiama Clan, Bayelsa State, Nigeria. - Nyingifa, Tonte; Gbuchie, Monica Anurika; Oboli, Deborah; Mkpae, Oluchi (International Journal of Medical Students, 2025)
BACKGROUND: The Gbarain/Ekpetiama clan is located in Bayelsa State, Nigeria, within the Niger Delta region, predominantly inhabited by the Ijaw people. School health services are essential for promoting the well-being of students and ensuring they are physically and mentally prepared to learn. However, the availability and quality of these services in secondary schools can vary significantly, especially in rural and underserved communities. This study aims to assess the presence and effectiveness of school health services in secondary schools within the Gbarain/Ekpetiama clan to understand how well these services support the health and education of students. METHODS: A descriptive cross-sectional study was conducted among 380 secondary school students and teachers in Gbarain/Ekpetiama clan, Bayelsa State. A multistage sampling technique was employed to select participants from various communities, schools, and classes. Data collection involved questionnaires and interviews with students, teachers, and principals. Ethical approval was obtained from the Ethics and Research Committee of the College of Health Sciences, Niger Delta University. Verbal consent was obtained from community leaders, school authorities, and teachers, while parental consent forms were provided for students. Data were analyzed using SPSS version 22.0, with results presented in frequency tables and summarized using proportions.Statistical significance was assessed using p-values, with a threshold of p < 0.05 considered significant. Key areas of analysis included the presence of essential health services, availability of first aid and sick bays, and the frequency of health inspections and screenings. RESULTS: The study found that 77.1% of the schools lacked formal school health services, and only 16.8% had essential drugs in their first aid boxes. A significant majority (95.3%) of schools did not have a functional sickbay, and 89.2% lacked a regular supply of drugs. Additionally, 94.2% of schools did not have a first aid box, and 95.8% had no emergency transport.( See table 1). Health education and routine medical screenings were also inadequate, with 88.7% of schools not conducting any screening activities. There were notable differences between public and private schools, with private schools generally having slightly better health services than public schools. CONCLUSION: The assessment reveals that the provision of school health services in the secondary schools of Gbarain/Ekpetiama clan is significantly lacking, especially in public schools. These inadequacies pose a risk to the health and academic performance of students. To achieve better health outcomes and educational success, it is crucial to enhance the availability and quality of health services in schools. Recommendations include assigning medical officers to oversee school health, implementing pre-admission medical screenings, and ensuring regular health education and services in all schools.